Edukasi Hukum Keluarga Islam Tentangn Khitbah Kepada Santri Pondok Pesantren Kreatif At-Taubah Di Desa Puncu Kediri - Ivayanti Ivayanti; Moch. Aziz Qoharuddin (LP3M IAIFA Kediri, 2021)
Sermon or is a prelude to a marriage, an act that is prescribed by Allah before the existence of a husband and wife bond with the aim that when entering marriage is based on research and knowledge and awareness of each party. Based on this context, the author carries out a program of mentoring to strengthen religious education in Islamic family law about sermons to students of the AT-TAUBAH creative Islamic boarding school in ds.puncu kec. The head of the district. Kediri. People who are able to get married (adults) through this are used as objects of action research because from initial observations it is seen that they meet the elements of the problem that are in accordance with the background that has been presented previously. The bond in the sermon occurs since the woman receives the sermon from the man, the sermon is just a marriage promise and not marriage. This is because marriage cannot be carried out unless the contract is valid. That way the men who apply and the women who are proposed are still other people. It is not lawful for the applicant to look at the woman except for the parts that are permitted by the Shari'a, namely the face and the two palms. Learning and introducing sermons well to people will certainly trigger enthusiasm and adequate efforts to carry out sermon activities in the community. Several roles have been carried out, the examples in question are identification and matters related to the sermon such as choosing the criteria for a partner, seeing their palms and faces (watching), between men and women explaining to each other how they and their families are.